The study on bond-slip constitutive model of steel-fiber high-strength recycled concrete. (December 2021) - He, Zhen-jun; Chen, Ying; Ma, Yan-ni; Zhang, Xiao-jie; Jin, Ying-xi; Song, Jia
Abstract: The central pull-out tests were performed on C60 steel-fiber high-strength recycled concrete (SFHSRC) under the monotonic load. The failure mode characteristic of the specimens and the direction of the cracks were observed and described. The bond strength and slip displacement were measured. The effects of two parameters, replacement ratio of recycled coarse aggregate (RCA) and addition ratio of steel fiber, on failure mode and bond-slip mechanicals behaviors of SFHSRC were also analyzed. The experimental results showed that when the replacement ratio of RCA was kept unchanged, the slip displacement of rebar increased with the increase of addition ratio of steel fiber, but the bond strength increased first and then decreased; with the addition ratio of steel fiber was remained unchanged, the bond strength and slip displacement of rebar decreased with the increased of the replacement ratio of RCA. The bond strength and slip displacement mentioned above reached the maximum when the steel fiber addition ratio was 0.8%; that is, when the replacement ratio of RCA was 0 and the addition ratio of steel fiber was 0.8%, the bond strength reached the maximum. Based on the theoretical analysis of experimental data, a reasonable bond-slip constitutive model was established in this paper, which can help promote more extensive application of RAC and realize persistent development strategy of building, resources and environment to a certain extent.